Design of 3D-printed hydroxyapatite intervertebral fusion cages in a patient specific framework - Anna De Cet; Martina Colombo; Luca D’Andrea; Ilaria Rota; Luigi La Barbera; Pasquale Vena; Dario Gastaldi (Medical & Biological Engineering & Computing, 2026)
Fusion surgery involves replacing degenerated intervertebral discs with artificial implants, usually composed of titanium alloys or PEEK, requiring bone grafting to assist tissue growth. This study aims to evaluate numerically 3D-printed porous ceramic implants as a bioactive alternative. Clinical computed tomographies of an adult patient were used to reconstruct the geometry and to assign mechanical properties to L1 and L2 vertebrae, utilizing a patient-specific anisotropic micromechanics-based model. The influence of different microstructural choices on a porous hydroxyapatite-based scaffold was analysed through finite element analysis, simulating standing and flexion. The analyzed scaffolds included: microstructured Face Centered Cubic (FCC) and Kelvin-based devices with uniform porosity (75%), and a Voronoi microstructured scaffold with uniform (75%) and graded porosity (60% external, 90% internal). Homogenized models were considered as a potential strategy to reduce computational costs. The FCC geometry and graded Voronoi proved more mechanically resistant to failure. Homogenized mechanical properties simplified the model, but didn’t accurately represent microstructural behaviour and local mechanical failure couldn’t be suitably identified. Patient-specific models allowed for a more accurate representation of mechanical stresses, leading to a reduced risk of structural failure. Hydroxyapatite proves to be a promising material for 3D-printed lumbar interbody fusion cages, able to provide primary stability.